RANCANG BANGUN PENDINGIN EVAPORATIVE LANGSUNG BERBAHAN SERAT BATANG PISANG DENGAN METODE VARIASI DERAJAT KEMIRINGAN - Anthoni Matahelumual; Anastas Rizaly (Universitas Muhammadiyah Surabaya, 2026)
In recent decades, the issue of energy crisis and environmental damage has hit the world and has an impact on the all aspects of human life. Thus, with this issue, energy saving became a major concern where air conditioning is not only the quality of the air that is a determining factor in whether a device is good or not. But the efficiency or amount of energy used and the impact on the environment are the important factors. So it is necessary to find the right solution to overcome the energy and environmental problems, one of which was cooling with a direct evaporative system. In this research process, a cooling pad has been used with a variation of the weave angle of 15 °, 30 °, 45 °. For the fluid cooler, water with room temperature had been used, and the air condition ranged from 35 ° C - 36 ° C. Data collection was carried out for a duration of 5 minutes, 10 minutes, 15 minutes. So that the results of the study obtained the direct evaporative Relative Humidity (RH) showing the difference in temperature with the wind speed on the fan is constant. The use of banana stem fiber pads with a 15° pad inclination angle could produce an ideal relative humidity (RH) of 45.5% compared to a 30° pad inclination angle of 42.2% and a 45° pad inclination angle of 39.34%. Where the ideal relative humidity (RH) according to health experts was in the range of 45% -65% using the standard Relative Humidity (RH) formula calculation listed in BMKG Regulation Number 04 of 2016 concerning Climate Observation and Management in the BMKG Environment.